Genetic mechanisms of antimicrobial resistance identified in Salmonella enterica, Escherichia coli, and Enteroccocus spp. isolated from U.S. food animals - Frye, Jonathan G.; Jackson, Charlene R. (Frontiers in Microbiology, 2013)
The prevalence of antimicrobial resistance (AR) in bacteria isolated from U.S. food animals has increased over the last several decades as have concerns of AR foodborne zoonotic human infections. Resistance mechanisms identified in U.S. animal isolates of Salmonella enterica included resistance to aminoglycosides (e.g., alleles of aacC, aadA, aadB, ant, aphA, and StrAB), β-lactams (e.g., blaCMY−2, TEM−1, PSE−1), chloramphenicol (e.g., floR, cmlA, cat1, cat2), folate pathway inhibitors (e.g., alleles of sul and dfr), and tetracycline [e.g., alleles of tet(A), (B), (C), (D), (G), and tetR]. In the U.S., multi-drug resistance (MDR) mechanisms in Salmonella animal isolates were associated with integrons, or mobile genetic elements (MGEs) such as IncA/C plasmids which can be transferred among bacteria. It is thought that AR Salmonella originates in food animals and is transmitted through food to humans. However, some AR Salmonella isolated from humans in the U.S. have different AR elements than those isolated from food animals, suggesting a different etiology for some AR human infections. The AR mechanisms identified in isolates from outside the U.S. are also predominantly different. For example the extended spectrum β-lactamases (ESBLs) are found in human and animal isolates globally; however, in the U.S., ESBLs thus far have only been found in human and not food animal isolates. Commensal bacteria in animals including Escherichia coli and Enterococcus spp. may be reservoirs for AR mechanisms. Many of the AR genes and MGEs found in E. coli isolated from U.S. animals are similar to those found in Salmonella. Enterococcus spp. isolated from animals frequently carry MGEs with AR genes, including resistances to aminoglycosides (e.g., alleles of aac, ant, and aph), macrolides [e.g., erm(A), erm(B), and msrC], and tetracyclines [e.g., tet(K), (L), (M), (O), (S)]. Continuing investigations are required to help understand and mitigate the impact of AR bacteria on human and animal health.